Telephone cardiopulmonary resuscitation is independently associated with improved survival and improved functional outcome after out-of-hospital cardiac arrest. (January 2018) - Wu, Zhixin; Panczyk, Micah; Spaite, Daniel W.; Hu, Chengcheng; Fukushima, Hidetada; Langlais, Blake; Sutter, John; Bobrow, Bentley J.
Abstract: Aim of study: This study aims to quantify the relative impact of Dispatcher-Initiated Telephone cardiopulmonary resuscitation (TCPR) on survival and survival with favorable functional outcome after out-of-hospital cardiac arrest (OHCA) in a population of patients served by multiple emergency dispatch centers and more than 130 emergency medical services (EMS) agencies. Methods: We conducted a retrospective, observational study of EMS-treated adult (≥18 years) patients with OHCA of presumed cardiac origin in Arizona, between January 1, 2011, and December 31, 2014. We compared survival and functional outcome among three distinct groups of OHCA patients: those who received no CPR before EMS arrival (no CPR group); those who received BCPR before EMS arrival and prior to or without telephone CPR instructions (BCPR group); and those who received TCPR (TCPR group). Results: In this study, 2310 of 4391 patients met the study criteria (median age, 62 years; IQR 50, 74; 1540 male). 32.8% received no CPR, 23.8% received Bystander-Initiated CPR and 43.4% received TCPR. Overall survival was 11.5%. Using no CPR as the reference group, the multivariate adjusted odds ratio for survival at hospital discharge was 1.51 (95% confidence interval [CI], 1.04, 2.18) for BCPR and 1.64 (95% CI, 1.16, 2.30) for TCPR. The multivariate adjusted odds ratio of favorable functional outcome at discharge was 1.58 (95% CI 1.05, 2.39) for BCPR and 1.56 (95% CI, 1.06, 2.31) for TCPR. Conclusion: TCPR is independently associated with improved survival and improved functional outcome after OHCA.